Anabolic steroids in patients undergoing total knee arthroplasty. Issue 5 (22nd September 2012) - Metcalfe, David; Watts, Evan; Masters, James P; Smith, Neil
Abstract : Objectives: To systematically review the evidence for using anabolic-androgenic steroids (AAS) to aid rehabilitation following total knee replacement (TKR). Design: Systematic review of all clinical study designs. Data sources: MEDLINE, EMBASE, AMED, CINAHL and the Cochrane Library were searched from inception to August 2012. Eligibility criteria: All clinical study designs without language or patient demographic limits. Outcome measures: All functional, physiological and administrative outcomes as well as reporting of adverse events. Results: Only two small randomised controlled trials satisfied the inclusion criteria. Statistically significant improvements were reported in the AAS group for quadriceps strength at 3 (p=0.02), 6 (p=0.01) and 12 (p=0.02) months, Functional Independence Measure score at 35 days (p=<0.05) and Knee Society Score at 6 weeks (p=0.02), 6 months (p=0.04) and 12 months (p=0.03). However, differences in hamstring strength, bone mineral density, sit-to-stand testing, walking speed, length of hospital stay and need for further inpatient rehabilitation did not reach statistical significance. There were no reported adverse events. Conclusions: There is insufficient evidence to recommend routine administration of AAS to patients undergoing TKR. However, pilot data suggest that AAS can be administered safely and may improve important postoperative outcome measures. This justifies a randomised trial sufficiently powered to identify between-group differences likely to be of clinical significance.